Multiyear Ground‐Based Measurements of Aerosol Optical Properties and Direct Radiative Effect Over Different Surface Types in Northeastern China. Issue 24 (26th December 2018) - Zhao, Hujia; Che, Huizheng; Xia, Xiangao; Wang, Yaqiang; Wang, Hong; Wang, Peng; Ma, Yanjun; Yang, Hongbin; Liu, Yuche; Wang, Yangfeng; Gui, Ke; Sun, Tianze; et al.
Abstract: Aerosol microphysical and optical properties as well as aerosol direct radiative effect (ADRE) were measured at a few ground sites to investigate aerosol optical‐radiative characteristics in northeastern China. Bimodal size distributions showed a dominance of fine mode particles at Shenyang, a megacity, and more impacts from larger particles at Fushun and Dalian, industrial and coastal sites, respectively. High aerosol optical depths at 440 nm in July (0.67–1.25) were ascribed to hygroscopic effects or cloud processing. Single scattering albedos at 440 nm show strong to moderate absorption at the urban and industrial sites (0.84–0.86) and weaker absorption at the coastal and rural sites (0.92–0.94). The single scattering albedo wavelength dependence implied influences of dust at the urban, industrial, and coastal regions (shorter wavelengths) and biomass emissions at the rural site (longer wavelengths). Absorptive aerosol optical depths at the urban and industrial sites were ~2.5 and 3.7 times higher than at the coastal and rural sites. Large negative ADREs at the bottom of the atmosphere at the urban and industrial sites implied strong surface cooling and the larger ADREs at the top of the atmosphere at the coastal site indicated more cooling of the Earth‐atmosphere system. The main aerosol types at the urban and industrial sites were mixed absorbing particles, while weakly‐absorbing fine mode particles dominated the coastal and rural sites. This study provides new information on the aerosol distributions and potential regional climate effects of aerosols in northeastern China. Key Points: High AODs in July were ascribed to hygroscopic effects in Northeast China The SSA440 nm show strong to slight absorption over the study region There is stronger surface cooling effect at the urban and industrial sites